Reliability analysis of the lateral torsional buckling resistance and the ultimate limit state of steel beams with random imperfections - Kala, Zdeněk (Journal of Civil Engineering and Management, 2015)
The paper deals with the analysis of reliability of a hot-rolled steel IPE-beam designed according to Eurocodes. A beam at its ultimate limit state is considered. The load acting on the beam consists of permanent and long-term single variation actions. The beam is loaded with end bending moments about the major principal axis. The beam is susceptible to lateral torsional buckling between the end supports. Reliability of the beam is assessed using probabilistic analysis based on the Monte Carlo method. Failure probability is a function of the random variability of the loadcarrying capacity and the random variability of load effects. The variability of the load-carrying capacity is influenced by the variability of initial imperfections. Imperfections are considered according to experimental research. Numerical studies showed that the failure probability is significantly misaligned. High values of failure probability were obtained for slender beams, for beams loaded only by permanent load action, and for beams loaded only by long-term single variation load. In further studies the values of partial safety factors of load and resistance were calibrated so that the failure probability had a target value of 7.2E–5. Relatively high values of partial safety factors were obtained especially for beams with high slenderness.